1
$\begingroup$

Assume that the equation is:

$a^2 y_0 -a^2 y_0 (y y_0)/b^2 =x y_0 x_0$

The form of the output equation is as follows: the right side of the equation equal sign is 1.

The desired result of the integral equation is:

$x x_0/a^2+y y_0/b^2 = 1$

$\endgroup$
1
  • $\begingroup$ sorry! I entered an extra plus sign $\endgroup$
    – csn899
    Jan 27 at 1:00

1 Answer 1

4
$\begingroup$
$Version

(* "13.2.0 for Mac OS X x86 (64-bit) (November 18, 2022)" *)

Clear["Global`*"]

eqn1 = a^2 y0 - a^2 y0 (y y0)/b^2 == x y0 x0;

eqn2 = SubtractSides[eqn1, eqn1[[1, 2]]]

(* a^2 y0 == x x0 y0 + (a^2 y y0^2)/b^2 *)

eqn3 = Assuming[eqn2[[1]] != 0,
  Simplify /@ DivideSides[eqn2, eqn2[[1]]]]

(* 1 == (x x0)/a^2 + (y y0)/b^2 *)

eqn4 = Reverse@eqn3

(* (x x0)/a^2 + (y y0)/b^2 == 1 *)
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.